Kidney diseases and long non-coding RNAs in the limelight - Liu, Chenxin; Ma, Kuai; Zhang, Yunchao; He, Xing; Song, Linjiang; Chi, Mingxuan; Han, Zhongyu; Li, Guanhua; Zhang, Qinxiu; Liu, Chi (Frontiers in Physiology, 2022)
The most extensively and well-investigated sequences in the human genome are protein-coding genes, while large numbers of non-coding sequences exist in the human body which are even more diverse and have more potential roles than coding sequences. With the unveiling of non-coding RNA research, long-stranded non-coding RNAs, a class of transcripts more than 200 nucleotides in length primarily expresses in the nucleus and a few in the cytoplasm, have entered our attention. LncRNAs are involved in various levels of gene regulatory processes, including but not limited to promoter activity, epigenetics, translation and transcription efficiency, and intracellular transport. It is dysregulated in various pathophysiological processes, especially in diseases and cancers involving genomic imprinting. In recent years, chronic kidney disease has become a significant global health burden, and numerous studies have linked lncRNAs to the pathophysiology of various kidney diseases such as chronic kidney disease, and membranous nephropathy, IgA nephropathy, unilateral tubal obstruction, and lupus nephritis. This review summarizes the molecular mechanisms involved in lncRNAs and their impacts on kidney diseases and its complications, as well as the value of lncRNAs as emerging biomarkers for the prevention and prognosis of kidney diseases, suggesting the potential of lncRNAs as new therapeutic tools.